Investment and Policy Framework Needed to Scale Digital Transformation of Egyptian Agriculture - (ICARDA), International Center for Agricultural Research in the Dry Areas (2024)
The present report provides information about the necessities for investment and policy framework to scale digital transformation in the agricultural sector of Egypt. The study has been performed on publicly available data from various private and public organizations, websites, and databases.